Teachers' Teaching Speaking Strategies at Junior High School - Krismardo Gea; Delsianti Dohude; Erikson Saragih (Institut Agama Islam Negeri Palopo, 2021)
This study aims to describe the teacher's strategy in teaching speaking skills to the students of SMP Dharma Pancasila Medan. This is done to find out what the teacher uses in teaching speaking skills to special class students at Smp Dharma Pancasila Medan, the strategies used by the teacher, as well as the problems and solutions faced in the implementation of teaching and learning. The methodology used in this study is a qualitative methodology. The research subjects were teachers at SMP Dharma Pancasila Medan. Data was collected through a questionnaire with an English teacher. The results showed that the strategy used by the teacher was only a question and answer strategy.Keywords: teacher’s strategies, speaking skills, English teacher.